Influence of thermophoresis and thermal radiation on mass transfer and heat of Three Dimensional maxwell fluid in presence of Magnetic field - Nidhal .M. AbdAlameer (Genius Journals, 2022)
The study is about Maxwell, three dimensions of non Newtonian fluid. Method of the Homotopy applied to analysis mass transfer and heat with thermophoresis effects
Keywords: Maxwell fluid; magnetic field; mass transfer